Inclusão escolar no período de 2009 a 2013 sob a perspectiva das matrículas no censo escolar no Brasil - Castro, Vanessa Dias Bueno de [UNESP] (2015)
Regarding the laws, decrees and recent educational policies in search of a non-exclusive school, the present study aimed to analyze the effects of Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva in relation to the number of enrollments of the target audience of special education in each Brazilian region, namely, North, Northeast, Southeast, South and Midwest, analyze the distribution of enrollments among the modalities of teaching and administrative offices from 2009 to 2013, using data obtained in Abstracts School Census Statistics and establish an overview of the scope of Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva in relation to enrollments. It's a research descriptive type. The results obtained and presented indicate that enrollments in basic education have been reduced in all regions. In relation to the students target audience of special education, all regions recorded sequences of significant increases in enrollments in Common Regular Education Classes. The Special Classes of Regular Education suffered reductions in enrollment in all five regions. The enrollments in Exclusively Specialized Schools in it's turn, were reduced in the North, Northeast, Southeast and Midwest and expanded in the South, hence, unlike the other regions, this region has recorded increased enrollments in Systems Segregated of Education. As conclusions, we can point out that the work reinforces the importance of data processed as a means for panoramas on the enrollments of the target audience of special education and consequently as a basis for the development of educational laws and policies, despite its limits. The data presented in the survey indicate that demand has grown and can grow in the coming years if the school continues to exclude, and then, in an attempt to reverse it, seeks to include them again. Therefore, it's necessary to broaden the discussion and raise ...